Using Two-Stay-Two-Stray Method to Increase the Speaking Ability in Procedure Text of the First Year Students of SMPN 6 Tambang - Dhea Intan Lestari Intan Lestari; FadlyAzhar Azhar; Erni ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This was an action research which conducted at SMPN 6 Tambang and started on April 2014 and ended on June 2014. The subject of this research was the first year students of SMPN 6 Tambang, particularly VII 1 consisted 22 students. The specific objective of this research is to know whether or not the use of two-stay-two-stray method can improve the students’ speaking ability and to know the factors cause the improvement. Besides, the researcher asked the collaborator to observe the process of the teaching and learning process by using the observation sheets prepared by the research. There were two kinds of research instruments used in this research which were test and observation. The test was used to collect the quantitative data and the observation sheet was used to collect the qualitative data.After accomplishing this research, the researcher concludes that the use of two-stay-two-stray method can improve the students’ speaking ability. It was clearly proven by the improvement in average score of the student from 45,45 (Pre-test) up to 62,85 (Post – test 1), then up to 78,36 (post-test 2). Moreover, based on the qualitative data that collected by the observer, the dominant factors caused the improvement of the students ability in speaking ability is the activeness of the students. Furthermore, by implementing two-stay-two-stray method, the students’behavior changed gradually from the ‘teacher-centered’ learning to ‘students-centered’ learning because they were allowed to work in group and help each other. In addition, this method also influenced the students to be more active while studying with two-stay-two-stray since they were free to express their idea about the text. Therefore, it was concluded that the use of two-stay-two-stray method could improve the students’ speaking ability. Keywords : Speaking ability, Two-Stay-Two-Stray method